2015
DOI: 10.1038/ni.3175
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, cellular origin and autoreactivity of antibody-secreting cell population expansions in acute systemic lupus erythematosus

Abstract: Acute SLE courses with antibody-secreting cells (ASC) surges whose origin, diversity, and contribution to serum autoantibodies remain unknown. Deep sequencing, autoantibody proteome and single-cell analysis demonstrated highly diversified ASC punctuated by VH4-34 clones that produce dominant serum autoantibodies. A fraction of ASC clones contained unmutated autoantibodies, a finding consistent with differentiation outside the germinal centers. A substantial ASC segment derived from a distinct subset of newly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
522
5
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 454 publications
(591 citation statements)
references
References 51 publications
(86 reference statements)
62
522
5
2
Order By: Relevance
“…In addition to a direct migration of AQP4 autoantibody‐secreting plasmablasts into the CNS compartment, we observed connections between CSF Ig peptides and peripheral blood memory, DN memory, and naïve VH transcripts indicating that additional maturation and differentiation of peripheral blood B cells into ASCs likely occurs within the CNS. Interestingly, a high degree of connectivity was observed between ASCs and activated naïve B cells in active systemic lupus erythematosus patients 12. Our data suggest that naïve B cells may also be actively recruited into the enhanced ASC response associated with NMOSD clinical relapse 16.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to a direct migration of AQP4 autoantibody‐secreting plasmablasts into the CNS compartment, we observed connections between CSF Ig peptides and peripheral blood memory, DN memory, and naïve VH transcripts indicating that additional maturation and differentiation of peripheral blood B cells into ASCs likely occurs within the CNS. Interestingly, a high degree of connectivity was observed between ASCs and activated naïve B cells in active systemic lupus erythematosus patients 12. Our data suggest that naïve B cells may also be actively recruited into the enhanced ASC response associated with NMOSD clinical relapse 16.…”
Section: Discussionmentioning
confidence: 65%
“…The stringency for CDR3 identity was chosen based on prior analysis of NMOSD CSF plasmablast clones1 that showed significant intraclonal CDR3 sequence variability. A similar approach was taken in the analysis of antibody‐secreting cell populations in systemic lupus erythematosus (SLE) 12. Lineage analysis (rooted B‐cell lineage trees) was performed using IgTree,13 kindly provided by Prof. Ramit Mehr.…”
Section: Methodsmentioning
confidence: 99%
“…This has been observed in multiple studies, suggesting differences in B‐cell selection and antigen‐specific B‐cell clonal expansion. All the BCR sequencing studies to date have shown an enrichment of IGHV4 gene family usages,17, 23, 35, 36 specifically IGHV4‐34 17, 36. IGHV4‐34 was the dominant serum autoantibody IGHV gene 17.…”
Section: Slementioning
confidence: 99%
“…This is characterized by polyclonal (multiple) B‐cell expansions 36. This is possibly secondary to increased numbers of plasmablasts.…”
Section: Slementioning
confidence: 99%
“…IGHV5‐51 is associated with Celiac disease 128129, 130, 131130 but it also has a unique framework 1 region that can bind to human red blood cell antigens I and i when in its germline form,132 these antigens can therefore be considered to be superantigens.…”
Section: Gene Use Analysismentioning
confidence: 99%